2001
DOI: 10.1006/geno.2000.6409
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of an Inner Ear-Expressed Human Melanoma Inhibitory Activity (MIA)-like Gene (MIAL) with a Frequent Polymorphism That Abolishes Translation

Abstract: To discover new cochlea-specific genes as candidate genes for nonsyndromic hearing impairment, we searched in The Institute of Genome Research database for expressed sequence tags isolated from the cochlea only. This led to the cloning and characterization of a human gene named melanoma inhibitory activity-like (MIAL; HGMW-approved symbol OTOR alias MIAL) gene. In situ hybridization revealed MIAL expression in a cell layer beneath the sensory epithelium of cochlea and vestibule of human fetal inner ear. No oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Recently, the extracellular protein OTOR, which has a high sequence identity and similarity to the human MIA protein, has been described [1][2][3]. Due to the high levels of sequence identity and similarity between MIA and OTOR we predict that OTOR also adopts an SH3 domain-like structure (Figs.…”
Section: Family Of Extracellular Sh3-domainsmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, the extracellular protein OTOR, which has a high sequence identity and similarity to the human MIA protein, has been described [1][2][3]. Due to the high levels of sequence identity and similarity between MIA and OTOR we predict that OTOR also adopts an SH3 domain-like structure (Figs.…”
Section: Family Of Extracellular Sh3-domainsmentioning
confidence: 95%
“…In the year 2000, a novel gene, OTOR (other designations: FDP (fibrocyte-derived protein), MIAL (MIA-Like)), was cloned by two experimental strategies and shown to be a close homologue of MIA [1][2][3]. Cohen-Salmon et al identified OTOR via subtractive cDNA screening in search for genes which are preferentially expressed in the inner ear.…”
Section: The Mia Protein Familymentioning
confidence: 98%
“…The protein MIA, which is strongly expressed in melanoma cells but not in melanocytes, is likely to represent a key molecule regulating melanoma progression (5,6). In 2000 OTOR [other designations: fibrocyte-derived protein (FDP), MIA-like (MIAL)], was cloned and shown to be a close homologue of MIA (7)(8)(9). Cohen-Salmon et al (7) identified OTOR via subtractive cDNA screening in a search for genes which are referentially expressed in the inner ear.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with their role in ionic and water transport, fibrocytes express various combinations of ion and water channels, carbonic anhydrases II and III (3,21,25,27,30), as well as gap junction connexins 26, 30, and 31 (7, 12, 37). The findings that fibrocytes also express extracellular matrix proteins (15,33,35) and proteins involved in cell-cell signaling, such as bone and cartilage morphogens (2,18,20,31) and the inner ear-specific cochlin, whose function is unknown (19), indicate a broader role and probably a diversity of specific functions that remain to be elucidated. The fact that the alteration of the fibrocyte integrity leads to pathology is an indication of their importance in inner ear physiology.…”
mentioning
confidence: 99%